Avaliação das eficiências técnicas das instituições de ensino superior (públicas e privadas) por meio da Data Envelopment Analysis (DEA) no período de 2004-2007 - Coelho Júnior, àlvaro Furtado (2011)
Education is one of the relevant points in the trajectory of a country towards development, with regard to higher education in recent decades, Brazil was characterized by an expansion of the units of higher education (public and private). In this scenario it becomes relevant to estimate performance indicators to guide decision making. One way to accomplish the estimation of efficiency indicators in sectors that have the participation of the public agent is through modeling nonparametric DEA. Since, in Brazil, until this study, there wasn t the application of classical DEA models for the assessment of simultaneous private and public sectors, where it employs a more judicious treatment in the selection of variables and DMUs to be analyzed, we attempted to if as objective of this work to fill this gap by measuring the technical efficiency of units of higher education (public and private), between the years 2004 to 2007, through the DEA BCC-O, and subsequent evaluation of the performance of IES, as well as the calculation of optimal values (targets) of the inefficient units that can support the planning of targets in the search for efficiency.